2007
DOI: 10.1002/path.2102
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and hearing loss

Abstract: Although many adults retain good hearing as they age, hearing loss associated with ageing is common among elderly persons. There are a number of pathophysiolological processes underlying age-related changes to functional components in the inner ear. Genetic factors determine the ageing process but are under the influence of intrinsic and environmental factors. It is difficult to distinguish changes of normal ageing from those of other contributing factors. The effects of age-related deafness can have significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
188
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(198 citation statements)
references
References 63 publications
(71 reference statements)
5
188
0
5
Order By: Relevance
“…Age-related hearing loss (AHL), characterized by a decline of auditory function with increasing age, is associated with attrition of spiral ganglion neurons and sensory hair cells in the cochlea of the inner ear (90,148). Studies have shown that CR delays the onset of AHL and reduces cochlear pathology (141,150) by reducing oxidative stress (150), which plays a major role in AHL (73,149).…”
Section: Sirt3 Prevents Hearing Loss During Crmentioning
confidence: 99%
“…Age-related hearing loss (AHL), characterized by a decline of auditory function with increasing age, is associated with attrition of spiral ganglion neurons and sensory hair cells in the cochlea of the inner ear (90,148). Studies have shown that CR delays the onset of AHL and reduces cochlear pathology (141,150) by reducing oxidative stress (150), which plays a major role in AHL (73,149).…”
Section: Sirt3 Prevents Hearing Loss During Crmentioning
confidence: 99%
“…Hearing loss is a hallmark of mammalian aging and is characterized by a gradual loss of spiral ganglion neurons and sensory hair cells in the cochlea of the inner ear, which is triggered by oxidative damage in these cells (12). Remarkably, CR prevents hearing loss and oxidative damage in wild-type mice, whereas Sirt3-deficient mice are resistant to the effects of CR.…”
Section: Agingmentioning
confidence: 99%
“…The theory is supported by the observations that over-expressing the mitochondrial antioxidant gene MnSOD [39] or the mitochondrial iron regulator protein frataxin [40] significantly increases longevity in Drosophila, while over-expressing a mitochondriallytargeted catalase gene results in reduced age-related pathology and moderately increased lifespan in mice [41]. Oxidative damage caused by ROS is also postulated to play a role in AHL [4,21,22]. Numerous studies have reported that ROS are generated in the cochlea exposed to noise of an intensity that leads to hearing loss [42,43].…”
Section: Delay Of Age-related Hearing Loss By Crmentioning
confidence: 97%
“…The mechanisms postulated to be responsible for the beneficial effects of CR on aging and AHL include reduced oxidative damage and reduced levels of mtDNA mutations [7][8][9][10][11][12][21][22][23][24][25]. Herein, we review the evidence that CR delays the onset of AHL in laboratory animals.…”
Section: Introductionmentioning
confidence: 99%